Effect of Surface Hardening on Dynamic Frictional Rolling Contact Behavior and Degradation of Corrugated Rail - Yuan Gao; Jingmang Xu; Ping Wang; Yibin Liu (Shock and Vibration)
The present study was undertaken to evaluate the effect of surface hardening technology on dynamic frictional rolling contact behavior and degradation of corrugated rail in Shenzhen. Characteristic parameters such as length and depth of corrugation were analyzed by means of a continuous measurement method based on the corrugation analysis trolley. The explicit finite element method for material hardening characteristics and real contact geometry was adopted to set up the 3D transient FE model of wheel and rail, after which the value and distribution of stress/strain as well as contact solutions could be obtained during frictional contact, and then the Archard wear model and simplified wear superposition method are integrated as a numerical simulation tool for rail wear after hardening. The simulation results show that laminar plasma surface hardening technology can increase residual stress and shear stress in quenched zones, leading to local stress concentration at their boundaries; the plastic strain in the matrix material is higher than that in the quenched zones, while the strain concentration is mainly focused on the matrix material. The hardening can remarkably reduce the rail wear along the corrugation wave, and the wear depth of material with hardening technology is about 36% of that of nonhardening material. Laminar plasma surface hardening technology can therefore restrain the development of rail corrugation.